Distributed leadership in practice in Finnish schools. (27th May 2017) - Lahtero, Tapio Juhani; Lång, Niina; Alava, Jukka
ABSTRACT: The aim of this study is to explore what aspects the principals and the members of the management teams in the primary and upper secondary education schools in Vantaa support distributed leadership in their school and how necessary they see that distributed leadership is extended to the students in matters concerning the curriculum and the development of teaching practices. The research method was a survey based on a questionnaire of 48 questions, where the respondents evaluated the preconditions of distributed leadership in their school. The principals and members of the management teams in the primary and upper secondary schools in Vantaa see distributed leadership mostly as delegation of predetermined tasks than the interaction among leaders, followers and situations. The results strengthen the view of distributed leadership as a phenomenon which in its primitive form can be seen in the official structures of the school and as delegation based on a formal position in the more advanced view distributed leadership can be seen as interaction among the management team and in the situations in the official and unofficial structures of the school.